Online Tourism Information and Tourist Behavior: A Structural Equation Modeling Analysis Based on a Self-Administered Survey - Majeed, Salman; Zhou, Zhimin; Lu, Changbao; Ramkissoon, Haywantee (Frontiers in Psychology, 2020)
This study presents the interacting phenomenon of perceived tourism destination’s online content (TDOC) and tourists’ behavioral intentions with a mediating role of tourists’ satisfaction, which is yet under-explored in hospitality and tourism research. A model based on three main constructs namely TDOC (with sub-constructs of online information quality and user-friendly accessibility), satisfaction, and tourists’ behavioral intentions (with sub-constructs of intentions to visit tourism destination and electronic word-of-mouth (eWOM), is presented to determine the growth of tourism business with the internet. Data were collected with the questionnaire-based survey from 413 tourists staying at hotels in Lahore city in Pakistan. Partial least square structural equation modeling was used to statistically analyze the gathered data. Findings indicate that tourists’ perceived TDOC directly influences their behavioral intentions while tourists’ satisfaction exerts a mediating influence between tourists’ perceived TDOC and their behavioral intentions. Taking advantage of an economical and widespread online environment, destination marketing organizations could attract more tourists with their confidence in TDOC and positive eWOM to remain competitive in the long run. Important theoretical and practical implications are discussed.